EVOLUTION OR TRANSFORMATION ? TRACING THE MINANGKABAU FOLKLORE IN MEME - Wasana Wasana; Satya Gayatri; Herry N Hidayat (LLDIKTI Wilayah X, 2022)
For the millennial generation, folklore is considered boring as a product of tradition. This generation prefers instant things and tends to avoid time-consuming processes. On the other hand, folklore is a product of tradition, which is more concerned with the process. However, it seems that folklore survives and even develops the following technological developments cross-generational. Folklore has adapted and changed into new forms in cyberspace. This article explains memes' visual variations and meanings with Minangkabau folklore content. There is a change in appearance and sense of folklore in internet memes. As a product of social practice, memes are also seen as an element of social processes. Therefore, this study uses social semiotics as an analysis tool. The result shows that in addition to showing creativity in building new folklore, memes also showed a shift in the understanding of traditional folklore. Memes also show the process and form of evolution of folklore so that it can survive in the rapid development of information technology. It contains hidden messages and statements in memes as a representation of attitudes towards social conditions and behavior.